PENGEMBANGAN KARAKTER MOBILE GAME PERANG PUPUTAN KLUNGKUNG - Putra, Putu Satria Udyana; Efendi, Mochamad Arman; Putu Wirayudi Aditama; Dwi Novitasari; I Nyoman Anom Fajaraditya Setiawan (Lembaga Pengembangan Kinerja Dosen, 2022)
Combining culture and technology is one solution to digitizing an area's local wisdom. Technology is expected to be an educational medium for the younger generation to know the history and meaning of a historical story. The island of Bali has a lot of the previous history, one of which is about the Puputan Klungkung war. Based on the results of questionnaires to 40 respondents by simple random sampling, 77.5% of respondents did not know the history of the Klungkung puputan and its meaning. To maintain the history of the puputan war, it is necessary to introduce the next generation but keep abreast of technological developments so that the research aims to design a media in the form of a mobile game. This mobile game media was chosen because of its popularity in Indonesian society, both among children to adults, thus creating interest in playing media games. The game design adapts to the scheme of the design pattern by using simple, cultured, and informative concepts. This development resulted in the design of the character of the king of Klungkung and the Dutch army and the layout design of the game Puputan Klungkung.